Childhood onset vitiligo − clinical profile and impact on quality of life of family members - Mary Augustine; Vimal John (Wolters Kluwer Medknow Publications, 2023)
Background: Vitiligo, a chronic disease, is distressing for patients and family. There are only a few studies on childhood onset vitiligo that describe its prognosis. Aim: To study the clinical and epidemiologic features of childhood onset vitiligo and to assess its impact on quality of life (QoL) of family members. Methods: A cross-sectional study was carried out on patients with vitiligo, with onset before 12 years of age. Clinicoepidemiologic profile was recorded. QoL of family members was assessed using family dermatology life quality index (FDLQI). Results: Fifty-four patients with age ranging from 1.2 to 41 years were included. Mean age of onset was 6.68 ± 3.43 years. Generalized vitiligo was most common (33.33%), followed by segmental (31.48%), acrofacial (24.07%), mucosal (7.40%), universal (1.85%), and focal (1.85%) types. About 42% had mucosal involvement, oral mucosa in 27.78%, and genital mucosa in 14.81%. Leukotrichia was significantly more common in segmental vitiligo (SV) than nonsegmental vitiligo (NSV) (P = 0.000046). Of the 9 adult NSV patients, progressive disease was reported in 6 with 10 years duration and 2 with 20 years duration. Mean FDLQI was 7.02 ± 3.64; emotional distress having maximum score (1.09). There was no significant association between total FDLQI and age (P = 0.69), gender (P = 0.528), clinical type (P = 0.874), vitiligo disease activity (VIDA) score (P = 0.105), or site of involvement (P = 0.07). Conclusion: NSV can be progressive for many years; a fact to be kept in mind while planning management of childhood onset vitiligo. QoL of family is affected regardless of the clinicoepidemiologic profile.